Global supply chain network design problem with rules of origin and limited import quotas. Issue 5 (27th April 2018) - Cheng, Xinxuan; Yang, Guoqing; Fan, Longfei
Abstract : Purpose: This paper aims to develop an uncertain global supply chain network design (GSCND) model with rules of origin (RoOs) and limited import quotas, and to discuss the international factors' effects on location decisions. Design/methodology/approach: The authors establish an uncertain GSCND model with the international factors. The transportation costs and customers' demands are characterized as random variables. To deal with the risk of uncertainty, the authors introduce the customers' demand service level. A sample approximation approach (SAA) is used to deal with the service level constraint and turn the proposed model into a mixed integer programming. On the basis of the properties of the proposed model, a hybrid memetic algorithm (MA) is designed to solve it. Findings: The authors find that the proposed MA is efficient to the real supply chain network design problem. Besides, the RoOs and limited import quotas can affect the optimal choices of plant and distribution center locations. Originality/value: The authors propose an uncertain GSCND model with RoOs and limited import quotas. An MA with SAA is designed to solve the proposed model. The authors apply the proposed model into a real global supply chain of an apparel corporation in East Asia, and give some managerial insights.